Synthesis and characterization of functionalized Se-MCM-41 a new drug carrier mesopore composite - Rahman, Md. Mokhlesur; Md Aris, Mohd Aznan; Yusof, Alias Mohd; Ansaryr, H.; Siddiqui, Mohammad Jamshed Ahmad; Yusan, S. (Oriental Scientific Publishing Company, 2017)
Various nanocomposite materials play a number of important roles in modern science and technology including pharmaceutical science. Among these materials, mesoporous materials cover a large number of applications in drug delivery system. The quantitative incorporation and high dispersion of selenium nanoparticles into MCM-41 have been made possible by the coordination between Se(IV) ion and aminopropyltriethoxysilane (APTES)-anchored MCM-41. The samples were characterized by X-ray powder diffraction, Fourier-transformed infrared spectroscopy (FTIR), scanning electron microscopy (SEM), nitrogen adsorption–desorption via multi-point Brunauer, Emmett and Teller (BET) analysis, Raman spectroscopy and UV-Vis diffusion reflection spectroscopy (UV-vis/DRS). The increase in cell parameter and the decrease in surface area observed by N2 adsorption-desorption technique were taken as evidence of selenium introduction inside the MCM-41 framework. The behaviour of drug release in these nanocomposites is probably due to hydrogen bonding interactions between drug and the hydroxyl group on the composite framework.